Pre-graduate medical education from the perspective of Primary Health Care: the Portuguese case - Santos, Paulo (Family Medicine & Primary Care Review, 2024)
Pre-graduate medical education intends to prepare future doctors for the practice of medicine. It is continually adjusted to the dichotomy between what doctors need to know and what patients actually need them to know. Each specialty wants students to learn a large number of specific subjects to understand the related diseases. Patients point out the need for doctors to overcome diseases through attitudes of person-centred care, professionalism, teamwork, leadership, cultural humility, a comprehensive approach and ethical commitment. In Portugal, healthcare and medical education organizations are still too hospital based. It is time to change and modernize future doctors to meet the needs of real people. We propose a renewed way to teach medicine based on the integrative vision of primary care, covering the holistic view, the global approach and the continuity of care. We argue that this makes it possible to better prepare future doctors for the challenges they will face in clinical practice over any other specialty’s relevant but partial perspective because of the proximity to the healthy person rather than the disease itself. It allows us to produce better doctors toward humanized medicine, closer to the people, without devaluing technological and organizational advances but placing them at the service of the patient.